Yang Hilang dari Pendidikan Kita: Jejak Pemikiran Syed M. Naquib Al-Attas - Muslimah, Ana; Khoir, Mulyanto Abdullah (Lembaga Yasin AlSys, 2025)
This study provides a comprehensive examination of Islamic educational thought according to Syed Muhammad Naquib al-Attas, a prominent Muslim intellectual renowned for his ideas on the Islamization of knowledge and the concept of adab as the core of education. The research is grounded in the relevance of Al-Attas’s educational paradigm as a response to the epistemological crisis afflicting contemporary education. Employing a qualitative, literature-based approach, the study begins with an intellectual biography of Al-Attas, followed by an analysis of key concepts in his thought, including the Islamic educational paradigm, his critique of the modern secular education system, the concept of adab, and strategies for the Islamization of knowledge. The findings reveal that Al-Attas not only presents a sharp critique of the dichotomy of knowledge and the erosion of values in modern education, but also offers an alternative framework that is holistic, spiritual, and rooted in the Islamic worldview. His concept of education based on adab represents a total transformation of the goals, structure, and values of education, positioning knowledge as a path to ma‘rifatullah and adab as the foundation for character formation. Thus, education according to Al-Attas functions as a principal instrument for building an authentic, resilient, and meaningful Islamic civilization amid global challenges.